2018
DOI: 10.1111/jphp.13054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carvacrol, Thymol and essential oils containing such monoterpenes on wound healing: a systematic review

Abstract: Objectives The treatment of wounds accounts for a considerable fraction of health expenses as well as serious socioeconomic problems. The use of natural substances stands out as a source of new therapeutic discoveries for the wound healing. Thus, this review compiled scientific findings on the applicability of carvacrol and thymol, or essential oils containing at least one of these compounds, for the treatment of wounds. Methods This review was performed at PubMed, SCOPUS, Web of Science databases using keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 72 publications
4
69
0
1
Order By: Relevance
“…Our results have also shown that tested Gram-negative bacteria (K. pneumoniae, P. aeruginosa, P. vulgaris, C. koseri) are sensitive to OR, TY, CA, CL, AR, and ME. Thymol, eugenol, and carvacrol have an antimicrobial effect against a broad spectrum of bacteria, namely Escherichia coli, Bacillus cereus, Listeria monocytogenes, Salmonella enterica, Clostridium jejuni, Lactobacillus sake, Staphylococcus aureus, and Helicobacter pyroli [15,22,23,26]. García-Salinas et al [46] found that the carvacrol, cinnamaldehyde, and thymol molecules contained in EOs could be used against E. coliand S. aureus-mediated infections, without a potential induction of bactericidal resistance and with lower cell toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results have also shown that tested Gram-negative bacteria (K. pneumoniae, P. aeruginosa, P. vulgaris, C. koseri) are sensitive to OR, TY, CA, CL, AR, and ME. Thymol, eugenol, and carvacrol have an antimicrobial effect against a broad spectrum of bacteria, namely Escherichia coli, Bacillus cereus, Listeria monocytogenes, Salmonella enterica, Clostridium jejuni, Lactobacillus sake, Staphylococcus aureus, and Helicobacter pyroli [15,22,23,26]. García-Salinas et al [46] found that the carvacrol, cinnamaldehyde, and thymol molecules contained in EOs could be used against E. coliand S. aureus-mediated infections, without a potential induction of bactericidal resistance and with lower cell toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Skin is the human body's primary barrier to the environment, and the first line of defense against microbial and chemical attacks [22]. Microbial infection is the most dangerous consequence of skin injury [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The results were in good accordance with several previous studies, including the study of Sivropoulou et al [32], which revealed 79.58% of carvacrol in Greek sourced O. vulgare essential oil and the study of Salvo et al [30], which revealed 26.33 ± 3.31% of carvacrol in O. vulgare essential oil from USA. The higher amount of carvacrol in HO (79.5%) compared to the carvacrol in CO (64.6%) and O. vulgare essential oils investigated in previous researches (23.43%-78.73%) should lead to superior biological activities, as carvacrol has been reported to have potent antibacterial, antifungal, antioxidant, free radical scavenging, anticholinesterase, and wound-healing activities [33][34][35][36][37][38].…”
Section: Chemical Compositions Of O Vulgare Essential Oilsmentioning
confidence: 92%
“…Moreover, thymol has also been reported as a therapy for wound repair. [36] In the samples of exocarp among the six varieties, the compositions of the main volatiles are almost identical. However, the amounts of volatiles in the mesocarp of FM and GQ are slightly larger than those in the ZhengMao series.…”
Section: Identification Of the Volatile Compoundsmentioning
confidence: 95%